IMPLEMENTATION OF THE CONCEPT OF LIFELONG LEARNING IN THE DIGITAL ERA PERSPECTIVE ABD AL-KARIM BAKKAR ON LECTURERS AND STUDENTS IN HIGHER EDUCATION - Maya, Rahendra; Sarbini, Muhammad; Samsuddin, Samsuddin; Arijulmanan, Arijulmanan; Fadilah Alfarisi, Muhammad (Edukasi Islami: Jurnal Pendidikan Islam, 2024)
Lifelong Learning or can also be expressed as Continuous Learning, in Islamic teachings is a big concept which is widely represented in the verses of the Qur’an and Hadith texts, as well as narrated by scholars and thinkers in their various opinions. Among contemporary scholars and thinkers who describe the concept of Lifelong Learning or Continuous Learning is Prof. Dr. ‘Abd Al-Karîm Bakkâr, M.A. in his various works, especially his work entitled Haula Al-Tarbiyah wa Al-Ta’lîm which is the primary data source in this research article. The research used in tis article is a type of qualitative research with descriptive-analytical literature study. Data collection uses documentation techniques and literature study, while analysis uses inductive-interpretative content analysis techniques. The result of the discussion show that ‘Abd Al-Karîm Bakkâr has a comprehensive concept of Lifelong Learning or Continuous Learning so that it is relevant to be implemented by lecturers and students in higher education in facing the digital era like today, through three strategies, namely (1) high motivation in learning-teaching, (2) enthusiastic about literacy, especially digital literacy, and (3) stepping into pedagogical-heutagogical-cybergogy learning.